MENINGKATKAN PERILAKU DISIPLIN ANAK USIA DINI DI ERA NEW NORMAL - Lestiawati, I Made; Sindu Putra, Ida Bagus Komang (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
ABSTRACT Â Discipline is a behavior that is based on obedience and compliance of the rules which apply at home, at the surrounding environment and the community in general. Discipline is grounded on a healthy and dynamic relationship between parenst and children. The first thing a parent must do before applying discipline to a child is to recognize the child as a whole. According to Soetjiningsih, the Effective Discipline Criteria for Early Childhood are: 1) Children feel it means or is important to themselves, 2) Obeyed and carried out with enthusiasm, 3) Effective for the long term, 4) Teaching life skills and valuable social skills for good characters (respect, care for others, be able to solve problems, like to work together), 5) Helping children to develop the belief that they have abilities. The importance of improving discipline behavior in the new normal era, specifically focused on how to educate early childhood to obey the new orders applies in the society. As the example, children are taught to keep their distance when traveling, washing hand or wearing hand sanitizer before and after holding something, always wear a mask when they are in public area and not to have physical touch with others. New rules during the covid-19 period bring an impact on the new lifestyle that prevailed in the general population. It becomes an important task for parents to provide understanding to children through discipline behavior that is applied starting from home. The most important thing in instilling and applying discipline in children is the creation of a warm (close)and loving relationship, also good communication between parents and children. By creating a good relationship, parents will be more easily to explain which things are allowed and should not be done by children, or which are good or not good for them. Avoid any unnecessary punishments, especially in the form of physical uses or unreasonable threats.Â